2008
DOI: 10.1111/j.1365-2826.2008.01726.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain Oxytocin: A Key Regulator of Emotional and Social Behaviours in Both Females and Males

Abstract: The neuropeptide oxytocin (OXT) is currently attracting considerable attention as a result of the discovery of the amazing behavioural functions it regulates, especially in the context of social interactions. A broad variety of behaviours, including maternal care and aggression, pair bonding, sexual behaviour, and social memory and support, as well as anxiety-related behaviour and stress coping, are modulated by brain OXT. These discoveries make this neuromodulator ⁄ neurotransmitter system of the brain a prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
449
2
19

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 654 publications
(479 citation statements)
references
References 115 publications
(149 reference statements)
9
449
2
19
Order By: Relevance
“…Oxytocin (OT), a peptide of the vasopressin and OT family, plays a critical role in social recognition and behavior in mammals from rodents to humans (Donaldson and Young, 2008;Neumann, 2008). This short polypeptide hormone is secreted dendritically from neurons in the paraventricular nucleus (PVN) and supraoptic nucleus (SON) of the hypothalamus and spread to other areas of the brain (McGregor et al, 2008;Skuse and Gallgher, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Oxytocin (OT), a peptide of the vasopressin and OT family, plays a critical role in social recognition and behavior in mammals from rodents to humans (Donaldson and Young, 2008;Neumann, 2008). This short polypeptide hormone is secreted dendritically from neurons in the paraventricular nucleus (PVN) and supraoptic nucleus (SON) of the hypothalamus and spread to other areas of the brain (McGregor et al, 2008;Skuse and Gallgher, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, additional research examining the context-specific effects that OT administration may have for analytical thinking is needed. Indeed, it seems plausible that in some contexts OT administration could benefit analytical task performance, perhaps via anxiety-reducing mechanisms (see Churchland and Winkielman, 2012;Neumann, 2008;Uvnäs-Moberg, 1998) or an enhanced approach orientation (De Dreu et al, 2013;Kubzansky et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…(Yamasue et al, 2009;Ebstein et al, 2009: Munesue et al, 2010MacDonald et al, 2011;Bartz et al, 2011). In rodents, OXT is highly involved in social interactions, social recognition, pair-bonding, and maternal behavior (Winslow and Insel, 2004;Insel and Fernald, 2004;Young and Wang, 2004;Young, 2007;Neumann, 2008;Donaldson and Young, 2008;Insel, 2010;Higashida et al, 2010). In addition, animal studies have shown that increased levels of OXT during the early postnatal period may affect behavior, and these effects may last into adulthood (Carter et al, 2009).…”
Section: Introductionmentioning
confidence: 99%